Program Penyediaan Air Minum Dan Sanitasi Berbasis Masyarakat Ditinjau Dari Komunikasi Pembangunan - Riva’i, Andi Kardian (Communiverse : Jurnal Ilmu Komunikasi, 2017)
It takes a driving force capable of mobilizing and directing the community's ability to realize the ideals of development, in this case the government as a communicator or source policy. The government intended in this research is the Riau Province Water Supply System Development Work Unit, Directorate General of Human Settlements, Ministry of Public Works and People's Housing as the party responsible for the implementation of Community-Based Drinking Water and Sanitation Program (Pamsimas). The flow of this research starts from the universal elements of communication ie S (Source), M (Messages), C (Channel), R (Receiver), E (Effect) which involves communication planning and organizational communication in addressing development issues. This research uses descriptive qualitative method with purposive sampling technique. Informant research as many as 5 people consisting of 1 person Head of Unit Development of Water Supply System, 1 staff chairman and 3 members of Pamsimas management. The results of this study indicate the improvement of communication quality characterized by information, motivation and education activities for the implementation of Pamsimas program which each stage experienced improvement and growth of the number of participants, mainly addressed to the villagers or poor with the provision of water and sanitation at low cost.